IMPLEMENTATION OF NSDI FOR DISASTER RISK MANAGEMENT IN INDONESIA : CASE STUDY ACEH PROVINCE - Widjojo, Suharto; Darmawan, Mulyanto (GEOMATIKA, 2011)
The Occurrence of the earthquake and tsunami on Sunday December 26, 2004 in the Province of Nanggroe Aceh Darussalam (NAD), the most western part of Indonesia, has been aware of Indonesian government that most part of their region are also prone area from earthquake and tsunami disasters. Long before, Central for Atlas of BAKOSURTANAL has shown an initiative toward providing easy access to geospatial data in a national context. The initiative was the development of national atlases, presenting the geographical information of a country in great detail and concise manner pertaining to the physical, culture and economical. This initiative was actually also to promote disaster awareness and provision of emergency aid in national level. However this is not the case, or at least not yet, Therefore, there was a significant confusion and concerns on the ground from international and local volunteer about Geospatial data during emergency response in 2005 in Aceh. The absence and difficulties in access to geospatial data were reason to the public an awareness of spatial information and access sharing during the disaster at the time. As of this, the idea of building a national and public infrastructure for accessing geospatial data has been discussed through the development of a national spatial data Infrastructure (NSDI). Therefore, provision of geospatial data and information to support disaster risk analysis is a step forward in the provision of multi hazard maps. This paper reviews the efforts made by BAKOSURTANAL in building NDSI for Disaster Risk Management support, based on geospatial team experience directly deployed in the field during the rehabilitation and reconstruction Aceh after the disaster. Keywords:  Geospatial data, National atlas, NSDI,  Disaster Risk Analysis schema scema  ABSTRAK Pasca Terjadinya gempa dan tsunami pada Minggu, 26 Desember Tahun 2004 di Provinsi Nanggroe Aceh Darussalam (NAD), bagian paling barat Indonesia, telah menyadarkan  Pemerintah Indonesia bahwa sebagian besar wilayahnya merupakan daerah rawan gempa dan bencana tsunami. Jauh sebelumnya BAKOSURTANAL telah menunjukkan inisiatif untuk menyediakan akses mudah ke data geospasial dalam konteks nasional dengan pengembangan atlas nasional yang menyajikan informasi geografis suatu negara dengan  rinci dan  ringkas berkaitan dengan budaya, fisik dan ekonomis. Inisiatif ini  akan bermanfaat pula untuk meningkatkan kesadaran tentang bencana dan penyediaan bantuan darurat di tingkat nasional. Karena atlas nasional tersebut belum selesai pada saat terjadinya bencana Aceh, ada kebingungan dan kekhawatiran di lokasi bencana dari relawan internasional maupun lokal tentang data Geospasial pada saat tanggap darurat pada tahun 2005 di Aceh.Sehingga muncul gagasan untuk membangun infrastruktur yang mampu mengakses data geospasial dan hal tersebut telah dibahas melalui pengembangan Infrastruktur Data spasial nasional (IDSN).Oleh karena itu, penyediaan data dan informasi geospasial untuk mendukung analisis risiko bencana adalah langkah maju dalam penyediaan peta rawan multi bencana. Tulisan ini membahas upaya yang dilakukan oleh BAKOSURTANAL dalam membangun IDSN untuk memberi dukungan terhadap Manajemen Risiko Bencana berdasarkan pengalaman tim geospasial yang langsung ditempatkan di lapangan selama masa rehabilitasi dan rekonstruksi Aceh setelah bencana. Kata Kunci: Data Geospasial, Atlas Nasional, IDSN,  Skema Analisis Risiko Bencana